Cancer deaths attributable to lifestyle risk factors in five Latin American countries - De Moraes-Ferrari, G; Ferrero-Hernandez, P (W B SAUNDERS CO LTD, 2026)
Objectives: Cancer is the leading cause of premature death in Latin America, driven largely by modifiable lifestyle factors such as poor diet, physical inactivity, alcohol intake and tobacco use. In this study, we estimated the burden of cancer deaths attributable to lifestyle risk factors in five Latin American countries. Study design: Comparative risks assessment modeling study. Methods: Data were obtained from national surveys Argentina, Brazil, Chile, Colombia, and El Salvador, comprising 259,327 adults aged 15 to >= 85 years. Lifestyle risk factors included fruit and vegetable consumption, physical activity, alcohol use, and tobacco. The Preventable Risk Integrated ModEl (PRIME) was applied to estimate the impact of these factors on cancer mortality under 75 years by sex. The model compared baseline distributions with counterfactual scenarios based on World Health Organization (WHO) recommendations to assess potential reduction in annual cancer deaths. Results: Women reported higher fruit and vegetable intake, whereas men were more physically active and had higher levels of alcohol consumption and tobacco use. Following WHO recommendations could prevent or postpone 103,217 deaths under 75 years (95 % uncertainty interval [95 % UI]: 92,577 to 113,659), with Brazil contributing to nearly half and Argentina over a quarter of them. Most averted deaths were among women, except in Colombia and El Salvador, where a higher proportion was observed among men. Lung cancer accounted for the largest share of preventable deaths (28,596, 95 % UI: 20,804 to 35,326), followed by stomach, esophageal, and pancreatic cancers. Conclusion: Promoting healthy lifestyle could significantly reduce or delay cancer deaths in individuals under 75 in Latin American countries.